Kepemilikan Benda Wakaf dan Akibat Hukumnya: Kajian Pendapat Ulama Mazhab - Hidayat, Rahmat (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article explained the differences of scholarly opinion regarding the ownership of waqf objects and their legal consequences. Where the object that has been entrusted is disputed by the scholars of the madhab its ownership status, it is still in the hands of the wakif or has moved to another party. The research method used library research and normative legal research with data collected from sunny school jurisprudence books and related books and articles. The data were analyzed comparatively. The results showed that Hanafi and Maliki scholars argued that the waqf object still belonged to the wakif, but the difference was if Hanafiyah allowed the wakif to withdraw the object that had been waqf, while Malikiyah did not allow it until the waqf period expired. Shafi'iyah and Hanabilah scholars argue that the object of waqf has come out of the ownership of the wakif to belong to Allah. The legal implication is that scholars differ in opinion about the istibdal waqf as a continuation of their differences in determining the owner of the waqf object. In addition, they also differ on term endowments, which of the four sunny schools, only Malikiyah allows it. Keywords: Istibdal; Possession; Scholars of the madhab; Waqf.